Analysis of the Complexities in the Water-Energy-Food Nexus: Ghana's Bui Dam Experience - Siakwah, Pius; Torto, Obodai (Frontiers in Sustainable Food Systems, 2022)
The quest to improve the mired development challenges of many developing economies and at a global scale have in recent years constituted policy imprimatur of development discourse, including the role of national/local resources. ‘Nexus’ is an ultra-prioritized integrative global development approach. It denotes connection(s) linking two or more phenomena or variables. It is therefore not surprising to witness the faddish approaches such as development-security nexus, migration-development-security nexus, water-energy nexus, among others. Particularly relevant to this chapter is the water-energy-food (WEF) nexus as an integrative strategy to tackle prosaic issues of industrialization, poverty reduction, food security and ecological sustainability. Adopting a qualitative methodological approach that entails documents, the chapter studies Bui dam to elucidate how the nexus actually operates in a complex and tensions environment. The central argument is most analyses of WEF interventions, particularly from the mainstream development literature rarely interrogate complex relational politics amongst the trident sectors (water, energy, and food). The dominant studies tend to dwell on the technical or instrumental aspects. But an understanding of complex relations needs a critical approach. Our key argument is that the WEF nexus is prominently embedded in historical complex systems that tend to counter-balance the hyper-deductive projected costs and benefits. Rather it is critical to view the relations amongst the WEF in a non-linear and realistic perspective. WEF is an embodiment of complex system helps us to understand the multi-level, contradictory, and diverse interests at play within, between and across the systems. We deem the WEF as a megaproject to fit into the complexity discourse. Even though the nexus operations on an assumption of seamless collaborative relations among and between institutions, agencies and actors in the policy and programme implementation space, the Bui project in Ghana shows tensions, side-lining and role conflicts among the actors, where the energy sector actors weigh power and resources over other institutions and actors in the space to drive the nexus